Psychological Features of Self-Realization in Chinese Students - - Chzhan Pan Hao (Peoples' Friendship University of Russia (RUDN University), 2013)
The empirical results of the research devoted to the problem of self-realization of students from China are discussed in the article, the specificity of the manifestation of separate variables in the structural organization of the said phenomenon is analyzed.